Simultaneous Biofortification of Rice With Zinc, Iodine, Iron and Selenium Through Foliar Treatment of a Micronutrient Cocktail in Five Countries - Prom-u-thai, Chanakan; Rashid, Abdul; Ram, Hari; Zou, Chunqin; Guilherme, Luiz Roberto Guimaraes; Corguinha, Ana Paula Branco; Guo, Shiwei; Kaur, Charanjeet; Naeem, Asif; Yamuangmorn, Supapohn; Ashraf, Muhammad Yasin; Sohu, Virinder Singh; et al. (Frontiers in Plant Science, 2020)
Widespread malnutrition of zinc (Zn), iodine (I), iron (Fe) and selenium (Se), known as hidden hunger, represents a predominant cause of several health complications in human populations where rice (Oryza sativa L.) is the major staple food. Therefore, increasing concentrations of these micronutrients in rice grain represents a sustainable solution to hidden hunger. This study aimed at enhancing concentration of Zn, I, Fe and Se in rice grains by agronomic biofortification. We evaluated effects of foliar application of Zn, I, Fe and Se on grain yield and grain concentration of these micronutrients in rice grown at 21 field sites during 2015 to 2017 in Brazil, China, India, Pakistan and Thailand. Experimental treatments were: i) local control (LC); ii) foliar Zn; iii) foliar I; and iv) foliar micronutrient cocktail (i.e., Zn + I + Fe + Se). Foliar-applied Zn, I, Fe or Se did not affect rice grain yield. However, brown rice Zn increased with foliar Zn and micronutrient cocktail treatments at all field sites, except for 3 sites. On average, brown rice Zn increased from 21.4 mg kg-1 to 28.1 mg kg-1 with the application of Zn alone and to 26.8 mg kg-1 with the micronutrient cocktail solution. Brown rice I showed particular enhancements and increased from 11 µg kg-1 to 204 µg kg-1 with the application of I alone and to 181 µg kg-1 with the cocktail. Grain Se also responded very positively to foliar spray of micronutrients and increased from 95 µg kg-1 to 380 µg kg-1. By contrast, grain Fe was not affected by the same cocktail spray at any field site, except for two sites. There was no relationship between soil extractable concentrations of these micronutrients with their grain concentrations. The results demonstrate that irrespective of the rice cultivars used and the diverse soil conditions existing in five major rice-producing countries, the foliar application of the micronutrient cocktail solution was highly effective in increasing grain Zn, I and Se. Adoption of this agronomic practice in the target countries would contribute significantly to the daily micronutrient intake and alleviation of micronutrient malnutrition in human populations.